2022
DOI: 10.1186/s13071-022-05392-7
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of vertical Hepatozoon canis transmission in dogs in Europe

Abstract: Background Hepatozoon canis is a protozoal agent that is known to be transmitted by oral uptake of H. canis-infected Rhipicephalus sanguineus sensu lato ticks in dogs. Vertical transmission of H. canis has only been described once in a study evaluating dogs from Japan. The aim of this study was to investigate the parasitological status of puppies from a bitch that had tested positive for Hepatozoon spp. prior to giving birth. Findings A 4-year-old,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
0
12
0
2
Order By: Relevance
“…In vertebrates, the transmission routes of Hepatozoon primarily include the ingestion of infected ectoparasites containing mature oocysts, often during grooming [ 15 , 16 , 41 , 42 ], and, to a lesser extent, the consumption of infected prey tissue carrying meronts or cystozoites (predation) or ectoparasites attached to their prey [ 43 46 ]. In mammals, transmission of macromeronts also occurs through the placenta (transplacental) [ 47 49 ]. However, this route was only confirmed in Hepatozoon canis , but it probably also occurs in Hepatozoon americanum [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…In vertebrates, the transmission routes of Hepatozoon primarily include the ingestion of infected ectoparasites containing mature oocysts, often during grooming [ 15 , 16 , 41 , 42 ], and, to a lesser extent, the consumption of infected prey tissue carrying meronts or cystozoites (predation) or ectoparasites attached to their prey [ 43 46 ]. In mammals, transmission of macromeronts also occurs through the placenta (transplacental) [ 47 49 ]. However, this route was only confirmed in Hepatozoon canis , but it probably also occurs in Hepatozoon americanum [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other studies also found a high prevalence in Sudan (42%), Ghana (40%), and Nigeria (41%) [19][20][21]. This characteristically high prevalence with wide distribution has been attributed to a large number of known vectors, including Rhipicephalus spp., and the potential for vertical transmission to puppies [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the ingestion of infected prey was confirmed as the route of infection for snakes or for Hepatozoon americanum in dogs [ 43 ]. Among the host population, the vertical path of infection, from mother to offspring, may be significant, as was proven for H. canis in dogs [ 44 ] or Hepatozoon erhardovae in voles [ 31 ]. Interestingly, we had three H. canis -positive puppies from one location, but we cannot confirm whether they were siblings born from an infected mother.…”
Section: Discussionmentioning
confidence: 99%